2015
DOI: 10.1159/000433523
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Specific Executive Functions and Falls Risk in People with Mild Cognitive Impairment and Early-Stage Dementia

Abstract: . (2015) The association of specific executive functions and falls risk in people with mild cognitive impairment and early-stage dementia. Dementia and Geriatric Cognitive Disorders, A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 28 publications
(36 reference statements)
2
35
0
Order By: Relevance
“…Prior studies [32] have shown that executive function plays a role in turning, but the domain of executive function may be too broad to provide meaningful results in a clinical or research context [33]. Processing speed is a more precise construct as it is a basic cognitive process that subserves higher-order cognitive domains such as executive function [34].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies [32] have shown that executive function plays a role in turning, but the domain of executive function may be too broad to provide meaningful results in a clinical or research context [33]. Processing speed is a more precise construct as it is a basic cognitive process that subserves higher-order cognitive domains such as executive function [34].…”
Section: Discussionmentioning
confidence: 99%
“…The Attention Switching Task assesses ability to ignore task-irrelevant and distracting information [28]. Outcome measures were switching cost and 7 congruency cost.…”
Section: Far Transfer Effectsmentioning
confidence: 99%
“…Deficits in this area may increase ataxia and the risk of falling in the postoperative period. 243,244 In a systematic review and meta-analysis investigating the adverse effects associated with long-term use of pregabalin, impaired coordination and cognition were the most common side effects, leading the authors to the conclusion that pregabalin may influence both vestibulocerebellar-and brainstem structures as well as higher cortical functions resulting in balance disorders and risk of falling. 245 Research have indicated that pain and cognitive functioning may interfere through actions on the same neuroanatomical and neurochemical structures.…”
Section: Cognitive Effectsmentioning
confidence: 99%